Behind bars: effects caused by incarceration on men deprived of liberty and health promotion actions within the prision system (Research, Society and Development, 2022)
This article proposes to analyze how health promotion actions occur and impacts of incarceration on men on prison system environment. It is a descriptive study with a qualitative approach. A data collection was carried out in a prison male located in a Northeast Region Brazilian, through conversation wheels with pre-established, dialogued exhibition, discussion of topics and dynamics of integration. The data they were analyzed descriptively, according to the following thematic categories: actions of promotion in health no prison scope; impacts of incarceration on men. The results indicate, from the perspective of the system prison, what exists the mechanism of social training of those who have some deviant conduct, for the purpose of resocialization. It's prison saint convergent os thoughts two arrested related to the prison health situation and impacts that incarceration impacts on re-educating, making strategies necessary aimed at greater empowerment and autonomy of these people no touching lawsuit health-disease, often neglected.